Launch of Vendor Business School Program to Empower Small Food Vendors in Quezon City, Philippines - Ricarte, Phoebe; Bertuso, Arma (CGIAR Initiative on Resilient Cities, 2024)
the CGIAR Resilient Cities initiative in partnership with the Quezon City Local Government Unit proudly launched its innovative Vendor Business School (VBS) Program. A total of 140 men and women small food vendors who will participate in the VBS program were recognized during the event. The VBS aims to empower small food vendors by providing them with vital knowledge, skills, and resources to tackle their everyday business hurdles and enhance their food safety measures. The VBS program is designed to guide and support vendors through training sessions and mentorship programs focused on entrepreneurship, business planning, budgeting, marketing, risk management, adapting to technological changes, establishing financial connections, and ensuring food safety.